Use of A Web-Based Application For Monitoring Changes in Elderly Knowledge on Oral Health Maintenance - Wahyudadi, Badai Septa; Ningtyas, Endah Aryati Eko; Benyamin, Benni; Rahayu, Umi Puji; Ijazati, Kholifah Nur (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
The results of the Basic Health Research (2018) stated that the Indonesian population with oral problems aged 55-64 years was 61.9% and aged 65 years was 54.2%. Some changes in teeth and oral cavity that are often found in the elderly are tooth loss which results in impaired food digestion, pain / pain in the teeth due to periodontal tissue and root caries, reduced vertical dimensions of artificial teeth, gingivitis and various other abnormalities. It is hoped that after being given oral health education through an innovation program in the form of a stroke elderly companion link or what is called “LIPSIAS” can increase the knowledge of stroke elderly on how to maintain their oral health through the help of a companion so that it can have a good influence on their dental hygiene. Research Objectives: Producing a dental and oral health maintenance program through empowering elderly companions in the form of the LIPSIAS Application as a medium for promoting oral health in the Elderly Social Service Home. Using Quantitative methods with pre-experiment research design (one group pretest and posttest design). The sampling technique was purposive sampling consisting of 14 elderly stroke at the Elderly Social Services Home. Results: The results of the statistical test showed P value 0.05, meaning that there was a significant difference in the knowledge of dental and oral health maintenance of stroke elderly before and after being given the LIPSIAS application intervention. Before treatment, the average value of knowledge of stroke elderly was 4.07 (poor category) increased to 8 (good category). The LIPSIAS application is effective in increasing the knowledge of stroke elderly about how to maintain oral health through companion assistance